Discovery of Novel Mono-Carbonyl Curcumin Derivatives as Potential Anti-Hepatoma Agents - Weiya Cao; Pan Yu; Shilong Yang; Zheyu Li; Qixuan Zhang; Zengge Liu; Hongzhuo Li (Molecules, 2023)
Curcumin possesses a wide spectrum of liver cancer inhibition effects, yet it has chemical instability and poor metabolic properties as a drug candidate. To alleviate these problems, a series of new mono-carbonyl curcumin derivatives G1–G7 were designed, synthesized, and evaluated by in vitro and in vivo studies. Compound G2 was found to be the most potent derivative (IC50 = 15.39 μM) compared to curcumin (IC50 = 40.56 μM) by anti-proliferation assay. Subsequently, molecular docking, wound healing, transwell, JC-1 staining, and Western blotting experiments were performed, and it was found that compound G2 could suppress cell migration and induce cell apoptosis by inhibiting the phosphorylation of AKT and affecting the expression of apoptosis-related proteins. Moreover, the HepG2 cell xenograft model and H&E staining results confirmed that compound G2 was more effective than curcumin in inhibiting tumor growth. Hence, G2 is a promising leading compound with the potential to be developed as a chemotherapy agent for hepatocellular carcinoma.